Philosophy as a Humanistic Discipline - Williams, Bernard, 1929-2003 (Book collections on Project MUSE., 2008)
What can--and what can't--philosophy do? What are its ethical risks--and its possible rewards? How does it differ from science? In Philosophy as a Humanistic Discipline, Bernard Williams addresses these questions and presents a striking vision of philosophy as fundamentally different from science in its aims and methods even though there is still in philosophy "something that counts as getting it right." Written with his distinctive combination of rigor, imagination, depth, and humanism, the book amply demonstrates why Williams was one of the greatest philosophers of the twentieth century. Spa